Mullerain anomaly with a persistent cloaca and an ovarian dermoid- a rare combination - Amatya, A; Gurung, G; Rana, A; Khakurel, MP; Singh, KP (Journal of Institute of Medicine Nepal, 2007)
Background: This case concerns a 30 year old unmarried woman who was least bothered by persistent cloacal opening in the perineum from which she had been passing stool, completely being ignorant of normal female anatomy of lower gastrointestinal/urogenital tract and only attended our hospital for combined operative management of cholelithiasis and ovarian dermoid detected by an ultrasound when she presented with 2 years history of abdominal pain. Case report: Laparotomy visualized mullerian anomaly in form of thumb sized uterus without a cervix and unilateral dermoid. Megacolon was also observed as a resultant of cloacal abnormality. Key words: persistent cloaca, mullerain anomaly, megacolon The full text of this paper is available at Journal of Institute of Medicine website